Isolation and Characterization of Irvingia gabonensis Seed Contents and the Tableting Properties of its Gum Component (Dhaka University Journal of Pharmaceutical Sciences, 2024)
This experimental work was designed to isolate, purify and estimate the fatty acids contents of Irvingia gabonensis seeds (IGS) and to evaluate the tableting properties of the gum constituent of the seed in metformin tablet. A known amount of the IGS was crushed and dispersed in purified water at a temperature of 80oC, Ethanol (90 %) was added, filtered and dried at 40oC. The fatty acid components were recovered using petroleum ether, while the gum was further purified with ethanol (90%). The fatty acid contents obtained were analyzed using an Agilent G1701 GC/MSD system. The gum content was evaluated using parameters such as: flow rate, angle of repose, bulk and tapped density and Carr’s index. The gum was granulated with other excipients and metformin powder dried at 40oC. The granules were evaluated as was done for the gum and tablet compression done at 2.0 KN on a single punch tablet machine fitted with 12.5 mm diameter die size. The GC-MS revealed bioactive compounds mainly fatty acids– lauric acid (36.82%), myristic acid (31.52%), benzyl dodecanoate (9.06%) and palmitic acid (4.03%), n-decanoic acid, 1-(hydroxymethyl)-1,2-ethanediyl ester, tetradecanoic acid, 2-hydroxy-1,3-propanediyl ester, etc. The granule size distribution revealed size and compactness in the following order: Acacia gum > IGS-gum > Gelatin, and average granule size for the batches were found to be 500 μm. Evaluation of metformin tablets gave the following results: crushing strength, friability, and disintegration time for B7 and B8 (7.5 and 10 %w/v IGS-gum as binder) as 58 and 68 N, 1.03% and 1.01%, 20.00 and 26.00 min., respectively. B3and B4 (7.5 and 10 %w/v acacia were shown as gum as binder) 44 and 48 N, 1.10 and 1.03%, 20.00 and 23.50 min., respectively. It can be concluded that at 7.5 and 10 %w/v, IGS-gum proved to be a better binder than acacia in metformin tablets formulation.Dhaka Univ. J. Pharm. Sci. 23(1): 53-62, 2024 (June)